Hydrothermal synthesis and tunable luminescence of NaBaPO4:Eu2+/Tb3+ phosphors. (December 2015) - Wei, Zhen; Guan, Jinyu; Song, Juanjuan; Xu, Yongchun
Abstract: NaBaPO4 :Eu 2+ /Tb 3+ phosphors were synthesized by the hydrothermal process. The phase structure of obtained samples was characterized by powder X-ray diffraction. The morphology and size were obtained by field emission scanning electron microscope. Under the excitation at 346 nm, NaBaPO4 :Eu 2+ /Tb 3+ phosphors exhibited the emission band originating from the 4f 6 5d 1  → 4f 7 transitions of Eu 2+ and the emission bands originating from the 5 D4  →  7 Fj transitions of Tb 3+ . The intensities and lifetimes of Eu 2+ decrease with increasing Tb 3+ concentrations. On the basis of luminescence properties of NaBaPO4 :Eu 2+ /Tb 3+ phosphors, we can conclude the energy transfer occurs between Eu 2+ and Tb 3+ in NaBaPO4 host. Highlights: The successful synthesis of NaBaPO4 :Eu 2+ /Tb 3+ nanorods. The tunable luminescence of NaBaPO4 :Eu 2+ /Tb 3+ by adjusting Tb 3+ concentration. The energy transfer between Eu 2+ and Tb 3+ in NaBaPO4 host.